The EU's Quest for Strategic Raw Materials: What Role for Mining and Recycling? - Edoardo Righetti; Vasileios Rizos (Intereconomics, 2023)
The war in Ukraine has brought the challenges stemming from Europe's dependency on natural gas and oil imports into sharp focus. This has also highlighted another dependency - that on raw materials that are critical for the EU's transition to a low-carbon economy. A strategic approach to raw material management can help negate the risks posed by a dependency on imports of critical raw materials. Improving resource efficiency is also necessary to achieve a low-carbon economy and sustain socio-economic progress in the face of finite natural resources. This Forum highlights the progress currently being made in geopolitical, economic and environmental areas and looks at the main constraints to the circular economy agenda where targeted solutions are needed. What is currently being done to decouple material consumption from welfare creation and use resources more efficiently? To what extent can recycling prolong the use of natural resources? Which measures can transform current business models into circular business models? How can technology and digitalisation be used to improve resource efficiency while minimising environmental burdens? Can knowledge transfer be used in addressing the complexity of the transition to a circular economy?
Keywords: L5; O2; O3; Q4; 330; Raw material; raw material supply; EU countries; Rohstoff; Rohstoffversorgung; EU-Staaten